ANALISIS PENGENDALIAN INTERN PENGGAJIAN DAN PENGUPAHAN PT JASA MARGA CABANG SURABAYA-GEMPOL - Susilowati, Ninik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
PT Jasa Marga (Persero) Surabaya-Gempol branch is a company which engages in the field of toll management service. This research is meant to find out how the implementation of internal control in salaries and wages at PT Jasa Marga (Persero) Surabaya-Gempol branch. Descriptive qualitative method is applied as the method of researchÂ  inÂ  thisÂ  researchÂ  byÂ  usingÂ  dataÂ  collection techniquesÂ  i.e.:Â  Interview,Â  documentation, observation.Â  The result of the research indicates that the internal control system in payment of salaries and wages which have been implemented by PT Jasa Marga (Persero) Surabaya-Gempol branch has been adequate since the company has fulfilled the elements of internal control i.e.: the firm separation of organization structure, record keeping and authorization system procedure, healthy practice, honest and competent employees, though there are some deficienciesÂ  ofÂ  freelanceÂ  attendanceÂ  monitoringÂ  systemÂ  whichÂ  stillÂ  usesÂ  writtenÂ  attendanceÂ  andÂ  checkÂ  clock machine, the error occurrence of permanent employeesâ fingerprint machine, and there is no monitoring from other divisions in the administrative department of Koperasi Karyawan PT Jasa Marga who works as time record keeping function also works as the wages list maker function. Keywords:Â Â  internal control system, internal control elements, payment of salaries and wages.